39th AIAA Fluid Dynamics Conference 2009
DOI: 10.2514/6.2009-4056
|View full text |Cite
|
Sign up to set email alerts
|

Transition Analysis for the HIFiRE-5 Vehicle

Abstract: The Hypersonic International Flight Research and Experimentation (HIFiRE) 5 flight experiment by Air Force Research Laboratories and Australian Defense Science and Technology Organization is designed to provide in-flight boundary-layer transition data for a canonical 3D configuration at hypersonic Mach numbers. This paper outlines the progress, to date, on boundary layer stability analysis for the HIFiRE-5 flight configuration, as well as for selected test conditions from the wind tunnel experiments supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…During descent, latest (highest Reynolds number) leading edge transition occurred when the diameter Reynolds number at the most upstream joint was 1. The minor axis (centerline) transitioned at a lower Reynolds number than the leading edge, which is consistent with prior CFD 69,70 and wind tunnel measurements 53,65 at hypersonic conditions that indicated that the centerline is more unstable and prone to lower Reynolds number transition. Centerline transition also showed a more gradual progression over time than the leading edge transition.…”
Section: Transition Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…During descent, latest (highest Reynolds number) leading edge transition occurred when the diameter Reynolds number at the most upstream joint was 1. The minor axis (centerline) transitioned at a lower Reynolds number than the leading edge, which is consistent with prior CFD 69,70 and wind tunnel measurements 53,65 at hypersonic conditions that indicated that the centerline is more unstable and prone to lower Reynolds number transition. Centerline transition also showed a more gradual progression over time than the leading edge transition.…”
Section: Transition Resultssupporting
confidence: 76%
“…This behavior indicates that the acreage transition appears to have been uninfluenced by tripped transition at the leading edge. The transition pattern agrees qualitatively with patterns observed in hypersonic wind tunnel experiments and computations 69,70 for hypersonic flight Mach numbers, with centerline transition occurring earlier than leading edge transition, due to the more unstable centerline boundary layer.…”
Section: Transition Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The results suggest that a transition N value of 4 and 6 for stationary and traveling crossflow modes, respectively, appears to give reasonable transition estimates off the leeward meridian of symmetry. These results are in line with a slender cone type configuration investigated within the same wind tunnel [15]. This paper provides preliminary analyses for transition over the wind tunnel models relevant to the MSL flight vehicle.…”
Section: Discussionsupporting
confidence: 63%
“…Each streamline shown in the figure starts at the onset of instability and extends to the location where a prescribed N value (4 for stationary crossflow and 6 for traveling crossflow instability modes) has been reached. The selection of 4 and 6 is based on the correlated stationary and traveling crossflow transition N-factor of the HIFiRE-5 vehicle model tested in the same NASA Langley wind tunnel [15]. The predicted transition fronts agree reasonably well with the off-axis transition patterns shown in Fig.…”
Section: Crossflow Instability Away From the Leeward Line Of Symmetrysupporting
confidence: 65%